Women with abuse-related posttraumatic stress disorder sleep more fitfully but just as long as healthy controls: an actigraphic study - Friedmann, Franziska; Hill, Holger; Santangelo, Philip S.; Ebner-Priemer, Ulrich; Neubauer, Andreas B.; Rausch, Sophie; Steil, Regina; Müller-Engelmann, Meike; Lis, Stefanie; Fydrich, Thomas; Priebe, Kathlen (Sleep, 2022)
Subjective reports of sleep impairments are common in individuals with posttraumatic stress disorder (PTSD), but objective assessments of sleep have yielded mixed results.We investigated sleep via actigraphy and e-diary on 6 consecutive nights in a group of 117 women with PTSD after childhood abuse (CA; PTSD group), a group of 31 mentally healthy women with a history of CA (healthy trauma controls, HTC group) and a group of 36 nontraumatized mentally healthy women (healthy controls, HC group).The PTSD group reported lower sleep quality, more nights with nightmares, and shorter sleep duration than both HTC and HC. Actigraphic measures showed more and longer sleep interruptions in the PTSD group compared to HTC and HC, but no difference in sleep duration. While the PTSD group underestimated their sleep duration, both HTC and HC overestimated their sleep duration. HTC did not differ from HC regarding sleep impairments.Sleep in women with PTSD after CA seems to be more fragmented but not shorter compared to sleep patterns of mentally healthy control subjects. The results suggest a stronger effect of PTSD psychopathology on sleep compared to the effect of trauma per se.Treating Psychosocial and Neural Consequences of Childhood Interpersonal Violence in Adults (RELEASE), https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00000000, German Clinical Trials registration number: DRKS00005578